Politics of liberation : paths from Freire - McLaren, Peter, 1948-; Lankshear, Colin (Routledge, 1994)
This book consists of a collection of original essays on the work of Paulo Freire, based on divers experiences of First and Third world contexts. All of authors argue that Paulo Freire is the cornerstone upon which a new vision and strategies of liberation can be built. The book offers a broad interpretive base addressing Marxist and post-socialist, modern and post-modern, hermeneutical, feminist and post-colonial perspectives.